2019
DOI: 10.1080/21691401.2019.1594243
|View full text |Cite
|
Sign up to set email alerts
|

pPolyHb protects myocardial H9C2 cells against ischemia-reperfusion injury by regulating the Pink1-Parkin-mediated mitochondrial autophagy pathway

Abstract: Zhu (2019) pPolyHb protects myocardial H9C2 cells against ischemia-reperfusion injury by regulating the Pink1-Parkin-mediated mitochondrial autophagy pathway,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Interestingly, BI1 reconstitution confers resistance for tubule cells to AKI-induced mitochondrial damage. Consistent with previous studies 45-48, the protective mechanisms exerted by BI1 in AKI involves elimination of cellular ROS, interruption of mitochondrial fission, and inhibition of mitochondrial apoptosis. Besides, based on our results, BI1 also plays unforeseen roles in sustaining mtDNA copy/transcription, mitochondrial respiration and mitophagy.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, BI1 reconstitution confers resistance for tubule cells to AKI-induced mitochondrial damage. Consistent with previous studies 45-48, the protective mechanisms exerted by BI1 in AKI involves elimination of cellular ROS, interruption of mitochondrial fission, and inhibition of mitochondrial apoptosis. Besides, based on our results, BI1 also plays unforeseen roles in sustaining mtDNA copy/transcription, mitochondrial respiration and mitophagy.…”
Section: Discussionsupporting
confidence: 89%
“…58 It has been reported that moderate mitochondrial serine/threonine protein kinase Pink1 and E3 ubiquitin protein ligase Parkin could effectively remove excess ROS and abnormal mitochondria to maintain cell stability, and resist apoptosis through mitochondrial phagocytosis. 60–62 On the other hand, during the process of mitochondrial autophagy, the damaged mitochondria are encapsulated in a bilayer membrane structure to form auto phagosomes. 63 If the scavenging reaction of auto phagosomes exceeds the protective threshold under the influence of external factors, mitochondrial autophagy will continue to occur and aggravate cell damage, leading to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The contraction and functioning of the heart are mainly dependent on mitochondria to provide energy. emerging evidence has suggested that the accumulation of dysfunctional mitochondria may result in increased intracellular roS, thus leading to cardiac dysfunction (42). Mitophagy is an effective process that can remove damaged mitochondria and maintain mitochondrial function (43).…”
Section: Discussionmentioning
confidence: 99%